Integration of the Vwa plasmid into the chromosome of Yersinia pestis strains harboring F' plasmids of Escherichia coli. - Zsigray, R M (1985)
Conditional virulent strains of Yersinia pestis were used as recipients of an F-lac plasmid from either Escherichia coli 23.10S or E. coli CSH23. The transconjugants of Y. pestis were calcium independent; however, calcium dependence was restored after the loss of the E. coli plasmid. The plasmid contents of several Y. pestis F-lac clones were compared with those of the parent strains and several lac segregants. Although the 6- and 61-megadalton plasmids were detected in all strains tested, the Vwa plasmid was absent in the F-containing strains. The plasmid was evident, however, in the lac segregants derived from the F-lac clones. Results of Southern transfers indicated that the Vwa plasmid had integrated into the chromosome of Y. pestis strains harboring F-lac.